A Collaborative Governance in the Net Zero Emission 2045 Program: A Case Study in Bali: Collaborative Governance dalam Program Net Zero Emission 2045: Studi Kasus di Bali - Bella Pratiwi; Gonda Yumitro (Jurnal Pemerintahan dan Politik, 2026)
Purpose : A case study is required in a region that has ambitious energy transition targets, faces the dilemma between economic development and environmental sustainability, and possesses a traditional governance system that interacts with a modern partnership framework. Design/methodology/approach : his research uses a qualitative approach with a document analysis method. Data was collected from official government documents, partner organization cooperation reports, and supporting scholarly articles. Findings : The findings show that the Program allocated IDR 12.5 billion from the provincial budget (APBD), while IDR 2.24 billion was allocated for Penglipuran from the Regency budget (APBD), village funds, and Corporate Social Responsibility (CSR). This funding resulted in rooftop solar power plants (PLTS) and communal biodigesters, leading to emission reductions. Practical Implication : his research recommends five policies for local governments in the energy transition: first, institutionalizing commitment through local regulations; second, hybrid financing; third, institutional capacity development; fourth, targeted subsidies; and fifth, sustained political support. Originality/value : The critical findings illustrate that collaborative governance is effective for incremental innovation (technology adoption, procedural improvements) but weak in driving structural transformation (power redistribution, institutional change).